Anion selective recognition and optical/electrochemical sensing by novel transition-metal receptor systems - Beer, P (1996)
Appropriately designed charged or neutral redox- and/or photo-active transition-metal organometallic and coordination receptor systems can selectively recognise and sense anionic guest species by electrochemical and/or optical methodologies. The topological positioning of the transition-metal Lewis-acid centres and of the ubiquitous hydrogen-bonding functionalities, such as amide (CO-NH) groups, dictates the anion selectivity trend and sensing proficiency the particular receptor displays.